Museum Architecture Matters - Jones, Paul; MacLeod, Suzanne (Museum and Society, 2017)
Using a series of illustrative examples throughout, we make an argument for the inclusion of sociological studies of museum architecture in museum studies, as well as advocating a series of methodological positions for future research. In short, the aim here is to provide students of both the museum and architecture with a route into the field - as well as a preliminary bibliography - while making the case for the need for increased engagement with the physical material of museums. Drawing on the widened scope of analytical possibilities represented by contemporary sociological analyses of architecture and the built environment, the paper sets forward an understanding of museum architecture as having a complex and entangled relationship with the museum institution and the variety of users of such (both actual and potential). Developing a threefold typology with the polemic intention to encourage increased research engagement with museums’ architectural forms, the paper is motivated by a desire to both showcase and advocate for the wide scope of analytical possibilities associated with sociological analyses of museum architecture. Key words: sociology; museums; architecture; design; material culture.